2019
DOI: 10.1177/1120700019841351
|View full text |Cite
|
Sign up to set email alerts
|

New drug, new problem: do hip fracture patients taking NOACs experience delayed surgery, longer hospital stay, or poorer outcomes?

Abstract: Non-vitamin K antagonist oral anticoagulants (NOACs) may affect patient outcomes. We aimed to evaluate whether hip fracture patients admitted on warfarin or NOAC therapy were at risk of operative delay, prolonged length of stay, or increased mortality. Methods We collected data for 845 patients admitted to our centre between October 2014 and December 2016. Multivariable linear regression analysis was performed to test the association between warfarin and NOAC therapy on time to surgery and length of stay. Vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 23 publications
(32 reference statements)
1
20
1
Order By: Relevance
“…Earlier hip fracture surgery has been associated with reduced LOS and reduced frequency of immobilization-related complications [ 25 28 ], and large resources have been applied to promote earlier surgical interventions [ 29 ]. Several studies have found increased surgical delay for DOAC-users [ 16 , 18 , 24 ], and the authors question whether the use of DOAC before the hip fracture results in unnecessary long surgical delay [ 14 , 24 , 30 32 ]. In contrast, our DOAC-using patients did not wait significantly longer for surgery than the non-users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier hip fracture surgery has been associated with reduced LOS and reduced frequency of immobilization-related complications [ 25 28 ], and large resources have been applied to promote earlier surgical interventions [ 29 ]. Several studies have found increased surgical delay for DOAC-users [ 16 , 18 , 24 ], and the authors question whether the use of DOAC before the hip fracture results in unnecessary long surgical delay [ 14 , 24 , 30 32 ]. In contrast, our DOAC-using patients did not wait significantly longer for surgery than the non-users.…”
Section: Discussionmentioning
confidence: 99%
“…Most guidelines advocate that hip fracture surgery should be performed within 48 h after admission, preferably within 24 h, to reduce the rate of medical complications and mortality [ 11 – 13 ]. Earlier studies have indicated that patients exposed for DOAC before the hip fracture wait longer for surgery than recommended in treatment guidelines [ 14 16 ]. The consequences of DOAC on semi-urgent surgery such as for hip fracture patients has not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown that DOAC treatment is related to a significant delay to surgery (beyond 36 hrs). 46 This problem is exacerbated by the confusion caused by the lack of consensus on the appropriate drug-free interval until hip fracture surgery. The British Society of Haematology recommends a 48-hour DOAC-free period prior to elective orthopaedic surgery in patients with normal renal function.…”
Section: Direct Oral Anticoagulants (Doacs)mentioning
confidence: 99%
“…It has been consolidated for years that early treatment within 48 hours allows for earlier mobilization and rehabilitation 7 . Many elderly patients with hip fractures, however, have several comorbidities, among which the most frequent are cardiovascular disease that require treatment with anticoagulants and can lead to delayed surgery 8 . The clinical outcome is generally poor with a one-year mortality of around 36% 9 .…”
Section: Introductionmentioning
confidence: 99%